Design and Performance Study of a Six-Bar Mechanism Underwater Robot Based on Cownose Ray Bionics - Yichen Chu; Xiaohan Wang; Tiancheng Hao; Yanhui Fu; Yubing Duan; Tianbiao Yu (Journal of Marine Science and Engineering, 2025)
This paper focuses on the formidable challenges that underwater robots encounter in complex marine environments. To address these issues, inspired by the cownose ray, an innovative scheme is proposed, utilizing four six-bar mechanisms to mimic its pectoral fin movement. Subsequently, the paper elaborates on the design, computation, and simulation of the bionic pectoral fin mechanism. A Watt-type six-bar mechanism is adopted, and by axially overlaying two scaled-identical mechanisms and setting a phase difference, the pectoral fin waving of the cownose rays is simulated. SolidWorks and ADAMS are employed for precise modeling and simulation. Following this, an experimental prototype is constructed, with the rod assembly produced by subtractive machining. Motion capture and six-dimensional force experiments are then conducted to evaluate its motion dynamics and propulsion efficacy. The experimental results demonstrate that when the two pectoral fins on either side flap synchronously or inversely, the robot can generate varying thrust, lift, and lateral forces, enabling smooth advancement and turning. These findings validate the feasibility and efficacy of bionic design, offering innovative concepts and methodologies for underwater robot development.

Regulating crystal face of SnO2 films for selective detection of H2 and DMC - Xun Shen; Jifeng Chu; Jianbin Pan; Aijun Yang; Jinyi Wang; Kehan Bo; Huan Yuan; Yichen Liu; Mingzhe Rong; Xiaohua Wang (Chemical Engineering Journal, 2025)

Starfish tube feet inspired hydrogel electrode for durable underwater sEMG acquisition - Yuanming Ye; Jun Guo; An Wang; Chengxiang Zheng; Tao Wu; Zhipeng Chen; Xuanqi Wang; Yichen Chu; Ruiyu Bai; Zekai Liang; Honglong Chang; Kai Tao; et al. (Chemical Engineering Journal, 2024)

Cenozoic structural and tectonic evolution in the Western Xihu Basin, East China Sea Shelf Basin - Bin Xu; Zhiping Wu; Yanjun Cheng; Johannes M. Miocic; Yining Dai; Yichen Chu (International Journal of Earth Sciences, 2024)

Structural characteristics and genetic mechanism of transfer zones in an extensional rift zone: An example from the Xihu Sag, East China Sea Basin - Yanjun Cheng; Zhiping Wu; Bin Xu; Jie Zhang; Yichen Chu; Yining Dai; Lili Xu; Wenjie Sun; Saiting Ma (Tectonophysics, 2023)

The Mesozoic tectonic evolution of the East China Sea Basin: New insights from 3D seismic reflection data - Yanjun Cheng; Zhiping Wu; Bin Xu; Yining Dai; Yichen Chu; Jie Zhang; Mingming Chen; Saiting Ma; Wenjie Sun; Lili Xu (Tectonophysics, 2023)

Strong partitioning of soil bacterial community composition and co-occurrence networks along a small-scale elevational gradient on Zijin Mountain - Xu Liu; Teng Yang; Yu Shi; Yichen Zhu; Mulin He; Yunke Zhao; Jonathan M. Adams; Haiyan Chu (Soil Ecology Letters, 2021)